2014
DOI: 10.1111/ecc.12180
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal barriers to participation in oncology clinical trials: factor analysis and correlates of barriers

Abstract: Patient participation in cancer clinical trials is low. Little is known about attitudinal barriers to participation, particularly among patients who may be offered a trial during an imminent initial oncology consult. The aims of the present study were to confirm the presence of proposed subscales of a recently developed cancer clinical trial attitudinal barriers measure, describe the most common cancer clinical trials attitudinal barriers, and evaluate socio-demographic, medical and financial factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
5
26
0
Order By: Relevance
“…Our findings support prior studies suggesting that financial concerns represent a major barrier to patient participation in cancer clinical trials [5,36,45]. In a study of 1,256 cancer patients assessing barriers to cancer clinical trial participation, worries about health insurance coverage of clinical care costs represented one of the strongest barriers [36].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings support prior studies suggesting that financial concerns represent a major barrier to patient participation in cancer clinical trials [5,36,45]. In a study of 1,256 cancer patients assessing barriers to cancer clinical trial participation, worries about health insurance coverage of clinical care costs represented one of the strongest barriers [36].…”
Section: Discussionsupporting
confidence: 88%
“…In a study of 1,256 cancer patients assessing barriers to cancer clinical trial participation, worries about health insurance coverage of clinical care costs represented one of the strongest barriers [36]. A second study, which sought to evaluate why patients decline cancer clinical participation, demonstrated that distance from the cancer center and insurance denial were common reasons for refusal to participate [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30,64 Similar to health care professionals, patients hold attitudes and beliefs that may also affect their willingness to participate and the way they communicate during clinic visits in which trials are discussed. 65,66 Despite this, research shows that, overall, minorities are as likely as whites to consent if they are offered a trial. 30,59,67,68 For example, an assessment of more than 4,000 racially diverse patients with cancer found no significant association between race and ethnicity and refusal to participate in a clinical trial or lack of desire to participate in research.…”
Section: Individual-level Barriersmentioning
confidence: 99%
“…Previous reviews have focused on challenges in conducting research with individuals who are at the end of life (Mackin et al, 2009; Steinhauser et al, 2006) or are very old (Townsley, Selby, & Siu, 2005) or with individuals participating in clinical trials for treatment of cancer (Lara et al, 2001; Manne et al, 2015; Wright et al, 2004). Ammari, Hendriksen, and Rydahl-Hansen (2015) described recruitment challenges and reasons for nonparticipation in a family-coping-oriented palliative home care trial with a population recruited from medical, surgical, and oncology hospital wards in Denmark.…”
Section: Introductionmentioning
confidence: 99%